2018
DOI: 10.17576/jsm-2018-4711-06
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity among Tomato Accessions based on Agro-Morphological Traits

Abstract: It is of great importance to know about the genetic diversity, conservation and classification for further utilization of tomato germplasm resources. Therefore, 40 tomato accessions were evaluated on the basic of agro-morphological traits for genetic diversity in 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
4
9
0
Order By: Relevance
“…PC1 accounted for 21.23 per cent of the total variation and almost all the characters under study showed positive loadings except days to flowering, days to 50% flowering, pericarp thickness, number of locules and single fruit weight. Hussain et al (2018) reported similar findings.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…PC1 accounted for 21.23 per cent of the total variation and almost all the characters under study showed positive loadings except days to flowering, days to 50% flowering, pericarp thickness, number of locules and single fruit weight. Hussain et al (2018) reported similar findings.…”
Section: Resultssupporting
confidence: 68%
“…Improving the above-mentioned traits will improve yield per plant indirectly. The results were on par with the findings of Hussain et al (2018) and De-Souza et al (2012).…”
Section: Cbesl118supporting
confidence: 71%
“…Meanwhile, volcanoes that erupt near to the poles or higher latitudes are uncertain whether they will cause cooling because the sulfurous aerosols are restricted to wind patterns around the poles (Sun et al, 2019). The total amount of solar radiation touching the earth surface varies by little margins as the energy released by the sun only differs by 1.3 W/m 2 which is associated with darker areas on the sun termed as sunspots (Hussain et al, 2018;Adnan et al, 2020). Approximately after every decade, the total number of darker areas on the sun changes from a maximum to a minimum number.…”
Section: General Background and Climate Change Statusmentioning
confidence: 99%
“…Sehgal [7] reported that total fruits per plant, days to 50 % flowering, pericarp thickness, plant height and days to first fruiting contributed more positively to PC. Hussain [13] reported that the traits such as day to 50% flowering, number of days to fruiting, number of fruits cluster-1, number of fruit plant-1, plant height, fruit length and fruit width contributed more positively to PC. Kumar [14] reported that days to 50% flowering, average fruit weight, pericarp thickness, plant height and fruit yield per plant contributed more positively to PC.…”
Section: Fig 1 Principal Component Analysismentioning
confidence: 99%